Science With Purpose: 50 Years of the Institute of Occupational Medicine - Seaton, Anthony; Cherrie, John W.; Cowie, Hilary; Aitken, Robert J. (Frontiers in Public Health, 2022)
The Institute of Occupational Medicine (IOM) was founded in 1969 by the then UK National Coal Board to complete its nation-wide epidemiological study of lung disease in coal miners, the Pneumoconiosis Field Research. The results quantified risks in the industry and were influential across the world in setting preventive standards. The research, based on epidemiology, was multidisciplinary from the start, and the IOM's broad scientific expertise was applied across many other industries with an increasing focus on environmental measurement and ergonomics. In 1990, as the coal industry declined, IOM became a self-funding research charity with a strong commercial arm. It has expanded its research, often with European collaborators and funding from governments, and has achieved wide recognition. This has most recently been applied during the pandemic in areas of hospital ventilation, personal protection, and viral exposure research, illustrating IOM's ability to respond to new environmental or occupational challenges.